Paw patrol. Pups chase a mystery [videorecording (DVD)] (Paramount Home Media Distribution, 2019)
Calling all Pups! Join Chase and the pups as they save a runaway stargazer! Next, the pups try to crack the mysterious case of a missing cellphone, and things get freaky when Chase and Chickaletta switch bodies. Then join Marshall, Skye, Zuma, and the whole team as they celebrate Chase's birthday and rescue Captain Gordy!